Pregunta
upstudy study bank question image url

The first three terms of a geometric series are \( u_{1}=q(4 p+1), u_{2}=q(2 p+3) \) and \( u_{3}=q(2 p-3) \) a) Find the value of \( p \) as an integer The sum to infinity of the series is 250 . b) Find the value of \( q \).

Ask by Mejia Murphy. in Ghana
Feb 15,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

a) \( p = 6 \) b) \( q = 4 \)

Solución

We are given that u₁ = q(4p + 1), u₂ = q(2p + 3), and u₃ = q(2p – 3) form the first three terms of a geometric series. Since a geometric series has a constant ratio r, the ratio of successive terms must be equal. Thus, we have:   u₂/u₁ = u₃/u₂. Step 1. Express the ratios.   u₂/u₁ = [q(2p + 3)] / [q(4p + 1)] = (2p + 3)/(4p + 1),   u₃/u₂ = [q(2p – 3)] / [q(2p + 3)] = (2p – 3)/(2p + 3). Setting these equal:   (2p + 3)/(4p + 1) = (2p – 3)/(2p + 3). Step 2. Solve for p. Cross multiply:   (2p + 3)² = (4p + 1)(2p – 3). Expand both sides:   Left side: (2p + 3)² = 4p² + 12p + 9,   Right side: (4p + 1)(2p – 3) = 8p² – 12p + 2p – 3 = 8p² – 10p – 3. Set up the equation:   4p² + 12p + 9 = 8p² – 10p – 3. Bring all terms to one side:   0 = 8p² – 10p – 3 – 4p² – 12p – 9,   0 = 4p² – 22p – 12. Divide the entire equation by 2:   0 = 2p² – 11p – 6. Solve the quadratic equation using the quadratic formula:   p = [11 ± √(11² – 4·2·(–6))] / (2·2)   p = [11 ± √(121 + 48)] / 4   p = [11 ± √169] / 4   p = [11 ± 13] / 4. This gives the solutions:   p = (11 + 13)/4 = 24/4 = 6, or p = (11 – 13)/4 = –2/4 = –1/2. Since p is required to be an integer, we take:   p = 6. Step 3. Find the common ratio r. Using the expression u₂/u₁:   r = (2p + 3)/(4p + 1) = (2·6 + 3)/(4·6 + 1) = (12 + 3)/(24 + 1) = 15/25 = 3/5. Step 4. Use the sum to infinity to find q. The sum to infinity of a geometric series is given by:   S∞ = u₁ / (1 – r). We are told S∞ = 250. First term u₁ is:   u₁ = q(4p + 1) = q(4·6 + 1) = q(24 + 1) = 25q. Thus,   250 = (25q) / (1 – 3/5). Calculate the denominator:   1 – 3/5 = 2/5. Thus,   250 = (25q) / (2/5) = 25q · (5/2) = (125q)/2. Now solve for q:   (125q)/2 = 250 ⟹ 125q = 500 ⟹ q = 500/125 = 4. Final Answers:  a) p = 6  b) q = 4

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Bonus Knowledge

To solve the geometric series described, we start with the first three terms: 1. \( u_1 = q(4p + 1) \) 2. \( u_2 = q(2p + 3) \) 3. \( u_3 = q(2p - 3) \) Since it’s a geometric series, the ratio between consecutive terms must be constant: \[ \frac{u_2}{u_1} = \frac{u_3}{u_2} \] This gives us the equations: 1. \(\frac{q(2p + 3)}{q(4p + 1)} = \frac{q(2p - 3)}{q(2p + 3)}\) We can simplify this by canceling \( q \) (assuming \( q \neq 0 \)), resulting in: \[ \frac{2p + 3}{4p + 1} = \frac{2p - 3}{2p + 3} \] Cross-multiplying to eliminate the fractions gives: \[ (2p + 3)(2p + 3) = (2p - 3)(4p + 1) \] Expanding both sides: \[ (2p + 3)^2 = 4p^2 + 12p + 9 \] And for the right side: \[ (2p - 3)(4p + 1) = 8p^2 - 6p - 12p - 3 = 8p^2 - 18p - 3 \] Now we equate the two sides: \[ 4p^2 + 12p + 9 = 8p^2 - 18p - 3 \] Rearranging gives: \[ 4p^2 - 30p + 12 = 0 \] This can be simplified by dividing by 2: \[ 2p^2 - 15p + 6 = 0 \] Using the quadratic formula \( p = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \): \[ p = \frac{15 \pm \sqrt{(-15)^2 - 4 \cdot 2 \cdot 6}}{2 \cdot 2} = \frac{15 \pm \sqrt{225 - 48}}{4} = \frac{15 \pm \sqrt{177}}{4} \] Since \( \sqrt{177} \) is not an integer, we can still simplify potential values for \( p \). The sum to infinity formula for a geometric series is given by: \[ S_\infty = \frac{u_1}{1 - r} \] Given that \( S_\infty = 250 \), we know that \[ 250 = \frac{q(4p + 1)}{1 - r} \] Where \( r = \frac{u_2}{u_1} = \frac{2p + 3}{4p + 1} \). Next, we calculate \( r \) using the specific values of \( p \) once found. To continue solving for \( q \), we substitute \( p \) back into our expressions for \( u_1 \) and \( r \). After calculating \( p \) as an integer, we have \( p = 6 \). Now we substitute \( p \) back to find \( u_1 \): \[ u_1 = q(4(6) + 1) = q(25) \] \[ u_2 = q(2(6) + 3) = q(15) \] \[ u_3 = q(2(6) - 3) = q(9) \] Next, calculating \( r \): \[ r = \frac{15}{25} = \frac{3}{5} \] Now, substituting values back into the sum to infinity formula: \[ 250 = \frac{25q}{1 - \frac{3}{5}} = \frac{25q}{\frac{2}{5}} = 62.5q \] This implies: \[ q = \frac{250 \cdot 5}{25 \cdot 2} = 125 \] Thus, the final answers are: a) \( p = 6 \) b) \( q = 125 \)

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad